Implementing Istanbul Protocol standards for forensic evidence of torture in Kyrgyzstan. (February 2015) - Moreno, Alejandro; Crosby, Sondra; Xenakis, Stephen; Iacopino, Vincent
Abstract: The Kyrgyz government declared a policy of "zero tolerance" for torture and began reforms to stop such practice, a regular occurrence in the country's daily life. This study presents the results of 10 forensic evaluations of individuals alleging torture; they represent 35% of all criminal investigations into torture for the January 2011–July 2012 period. All individuals evaluated were male with an average age of 34 years. Police officers were implicated as perpetrators in all cases. All individuals reported being subjected to threats and blunt force trauma from punches, kicks, and blows with objects such as police batons. The most common conditions documented during the evaluations were traumatic brain injury and chronic seizures. Psychological sequelae included post-traumatic stress disorder and major depressive disorder, which was diagnosed in seven individuals. In all cases, the physical and psychological evidence was highly consistent with individual allegations of abuse. These forensic evaluations, which represent the first ever to be conducted in Kyrgyzstan in accordance with Istanbul Protocol standards, provide critical insight into torture practices in the country. The evaluations indicate a pattern of brutal torture practices and inadequate governmental and nongovernmental forensic evaluations. Highlights: The study represents 35% of the investigations into torture from 01/2011 to 07/2012 in Kyrgyzstan. All individuals were male and all reported being subjected to threats and blunt force trauma. Traumatic brain injury and chronic seizures were the most common physical sequelae. Posttraumatic stress disorder and major depression were the most common psychological sequalae. First set of evaluations conducted in Kyrgyzstan in accordance with Istanbul Protocol standards.